Unraveling the Nexus Between Organizational Culture and Teachers’ Organizational Commitment in Private Tertiary Institutions - Alicante-Marte, Estella Marie (East Asian Journal of Multidisciplinary Research, 2024)
In this quantitative study, a descriptive-correlational research design was employed to assess the levels of organizational culture and organizational commitment among 100 teachers in private tertiary institutions in Tagum City, Philippines. The study aimed to determine if a significant relationship existed between these variables. Data collection involved the utilization of two survey questionnaires, with analysis conducted through frequency counts, percentages, means, and Pearson correlation coefficient (r). Findings indicated a high level of both organizational culture and organizational commitment, with a positively moderate relationship between them. The relationship between respondents' organizational culture knowledge and organizational commitment was particularly significant. These results underscored the importance of organizational culture in shaping teacher commitment in educational settings.